Associação entre o perfil antropométrico, adipocitocinas e a resposta ao tratamento neoadjuvante de pacientes com diagnóstico primário de câncer de mama - Freitas, Gisely de Lima (2024)
Breast cancer (BC) is the most common cancer among women worldwide, with excess adiposity being an extrinsic factor linked to its development, associated with the inflammatory state resulting from obesity and the imbalance of adipocytokines arising from adipose tissue. The objective of this study was to investigate the association between serum levels of adipocytokines and the development of resistance to neoadjuvant treatment in BC patients. Based on clinical and metabolic parameters, 81 patients, aged 18 to 85 years, with a primary diagnosis of BC, undergoing the doxorubicin/cyclophosphamide/taxol (AC-T) protocol were analyzed. We analyzed the patients according to the World Health Organization criteria for body mass index (BMI) and anthropometric measurements. We divided the clinical responses into two groups: complete response (CR) and non-response (NR). Blood samples were collected from all 81 patients three times: pre-chemotherapy, after four sessions of AC, and after two sessions of taxol, for resistin, leptin, and adiponectin measurements by enzyme-linked immunosorbent assay (ELISA). Statistical analysis was performed using SPSS® software, version 20.0, and GraphPad Prism version 9.0. The results showed a mean age of 51.60 years (±12.03). After treatment with NT in the 81 patients, there was an increase in plasma levels of resistin (4565 ± 1136; P<0.05) compared to pre-NT collections (4376 ± 1207; P<0.05). There was no difference in mean age or BMI between the groups before CT. Regarding the clinical response, there was no significant difference between BC patients with CR (4,623 ± 813.6) and NR (4,550 ± 1,207). Those with BC without response to NT and with resistin levels above the median cutoff point have higher levels of this hormone (5582±380.9; P<0.05) compared to patients with CR (5175±183.5). It was observed that obese patients have elevated levels of resistin compared to non-obese patients analyzed by Heatmap (P<0.05). In addition, when performing correlation analysis, it was possible to observe that leptin concentrations are influenced by BMI (p=0.025) and hip circumference (p= 0.048) before treatment, and that adiponectin correlates with PCT after AC (p=0.006), and especially with visceral adiposity markers, before and after chemotherapy, showing statistical significance between collections, such as WC (p=0.008; p=0.017, respectively); conicity index (p=0.024; p=0.029); waist/hip ratio (p=0.000; p=0.001, respectively). Therefore, we conclude that increased levels of abdominal adiposity and resistin are associated with resistance to NT in BC patients.